Le travail en bulles - Martine Gasparov; Émilie Boudet; Isabelle Chambost; Lucie Goussard; Joyce Sebag (La Nouvelle Revue du Travail)
The publication of a comic strip on the theme of work in philosophy is an opportunity to analyze with the author and illustrator of this work how the philosophical concept of Work can be put into a comic strip, and how the latter is likely to enable a different and complementary appropriation of philosophical concepts. These interviews are also an opportunity to study the collaborative work and task-sharing arrangements between authors and illustrators, as well as the working conditions and remuneration of a comic strip that is part of an after-school collection published by two publishers, Belin and la Boîte à Bulles.